Mechanisms and Regulation of the Mitotic Inheritance of the Golgi Complex - Valente, Carmen; Colanzi, Antonino (Frontiers in Cell and Developmental Biology, 2015)
In mammalian cells, the Golgi complex is structured in the form of a continuous membranous system composed of stacks connected by tubular bridges: the “Golgi ribbon”. At the onset of mitosis, the Golgi complex undergoes a multi-step fragmentation process that is required for its correct partition into the dividing cells. Importantly, inhibition of Golgi disassembly results in cell-cycle arrest at the G2 stage, which indicates that accurate inheritance of the Golgi complex is monitored by a ‘Golgi mitotic checkpoint’. Moreover, mitotic Golgi disassembly correlates with the release of a set of Golgi-localised proteins that acquire specific functions during mitosis, such as mitotic spindle formation and regulation of the spindle checkpoint. Most of these events are regulated by small GTPases of the Arf and Rab families. Here, we review recent studies that are revealing the fundamental mechanisms, the molecular players, and the biological significance of mitotic inheritance of the Golgi complex in mammalian cells. We also briefly comment on how Golgi partitioning is coordinated with mitotic progression.